Before sunset - Krizan, Kim; Daniel, Lee 1962-
Two strangers met by chance, spent a night together in Vienna, and parted before sunrise. Nine years later, Jesse has written a book about the encounter. During his accelerated European book tour, he meets up with Celine in Paris. Before Jesse's flight home, he joins Celine for a picturesque walk around the city and they have an intimate conversation, ending at Celine's apartment. Will they get the chance to fall in love all over again?
Bildformat: 1.85:1 (16:9)
Orig.: USA 2004
Enth. Am Set von Before sunset
Keywords: Authors - Drama; Autores - Teatro; Conversation - Drama; Man-woman relationship - France - Paris - Drama; Relaciones hombre-mujer - Francia - París - Teatro; Authors -- Drama; Conversation -- Drama; Love -- Feature.; Man-woman relationships -- France -- Paris -- Drama; Frankreich; Feature films; Video recordings for the hearing impaired; Romance - Feature